Solve the system by the elimination method.
x + y - 6 = 0
x - y - 8 = 0
When you eliminate y , what is the resulting equation?

Respuesta :

irspow
Since we have a positive y in one equation and a negative y in the other, we can simple add the two together to eliminate y...

2x-14=0

2x=14

x=7, which makes x+y=6 become:

7+y=6

y=-1, so the solution to the system of equations is the point:

(7, -1)

Answer: 2x = 14

Step-by-step explanation:

Solving the equation us in elimination method,

x + y - 6 = 0...1

x - y - 8 = 0...2

From 1,

x+y = 6...3

x-y = 8...4

To eliminate y, we will add equation 3 and 4 since both the signs attached to y are different.

2x=6+8

2x = 14 (This will be the resulting equation)

To get the variables x, we will divide both sides of the resulting equation by 2

x = 14/2

x = 7

Substituting x = 7 into eqn 3

7 + y = 6

y = -1